Modulating Fish Gelatin Gelling Properties Through Furcellaran Addition: A Structural and Physicochemical Analysis - Tanyamon Petcharat; Manat Chaijan; Sylvia Indriani; Jaksuma Pongsetkul; Supatra Karnjanapratum; Sitthipong Nalinanon (My University, 2025)
Fish gelatin (FG) is a promising alternative to mammalian gelatin but is limited by poor gelling ability, low gel strength, and inability to set at room temperature. This study evaluated the effects of furcellaran (FUR), a gelling agent, on the structural and physicochemical properties of FG gels at different substitution levels (25–100%). The addition of 25% FUR improved gel strength and hardness. However, higher FUR levels (>50%) led to reduced springiness and increased syneresis. Intermolecular force measurements revealed that ionic and hydrogen bonds were crucial in the FG/FUR gel system, with higher levels of FUR promoting stronger ionic and hydrogen bonding. Color changes were observed with decreased L* and increased b* and ∆E* values as FUR levels rose. Gelling and melting points also increased proportionally with FUR content. Microstructural analysis showed denser gel networks with smaller gaps upon FUR incorporation. SAXS analysis confirmed enhanced structural conformation with higher FUR levels. An appropriate level of FUR added (25%) could therefore improve gelling properties via increasing gel strength and gelling temperature without negative effects on springiness and syneresis of resulting gel.
Keywords: Gelatin; Collagen: Extraction and Characterization